Contemporary perspectives on organizational social networks - Brass, Daniel J. (Research in the sociology of organizations ;, 2014)
Social network analysis has transformed the study of organizations over the past 30 years. Rather than focus on individuals or teams, network scholars view the organization as a nexus of relationships. As its popularity increases, the scholarship is evolving in many directions including new theory on network dynamics, multilevel thinking, multiplex networks, digital networks, instrumental and affective ties, and cross-cultural considerations, in addition to advances in methods and measures, and new organizational applications. This compendium of essays points the way to contemporary issues in organizational social networks.Research in the Sociology of Organizations is an established international, peer-reviewed series that examines cutting edge theoretical, methodological and research issues in organizational studies. The series is especially concerned with specifying the unique contributions of sociological theories and research techniques to the analysis of organizations. In addition to publishing high quality original research, each volume aims to foster debate about the value of new theories and research to the growing international community of organizational studies scholars.